Predictive modeling of molecular interaction energies using topological and spectral entropies of zeolite AWW - Peter, Pancras; Clement, Joseph; Arockiaraj, Micheal; Jacob, Kavin (Frontiers in Chemistry, 2025)
Zeolites are extremely massive mineral crystals with complex frameworks, composed of internal porous structures with channels and cages. Open-framework aluminophosphates (AlPOs) are a significant class of inorganic crystalline compounds known for their diverse properties. Our study focuses on the topological aspects of zeolite frameworks using graph theoretical techniques, providing insights into computational chemistry. In this article, we compute various degree-based topological indices, information entropy, and spectral entropies of zeolite AWW using the bond partitioning approach to assess the complexity of the framework. Additionally, we present the HOMO–LUMO gap measures to evaluate the global chemical descriptors using the eigenvalues of the adjacency matrix of zeolite structures. Furthermore, we developed exponential and polynomial regression models using the obtained information entropy and spectral values to predict various potential energies of the framework. Based on the outcomes of the study, we infer that the information entropies and spectral value have a significant relationship with the potential energies.